Estratégias para a síntese de agregados reticulados porosos de lipase de pâncreas de porco com propriedades magnéticas - Guimarães, José Renato (2019)
Cross-linked enzyme aggregates (CLEAs) is an immobilization technique that does not require solid support, allows the use of semi-purified enzymes and the biocatalyst show higher volumetric activity. However, they present low mechanical resistance, difficulty of recovering and intraparticle diffusion limitations. To overcome these problems, the preparation of highly porous magnetic crosslinked aggregates (pm-CLEA) of porcine pancreas lipase (PPL) is reported. Some strategies to improve the volumetric activity of the immobilized biocatalyst were evaluated, such as treatment of PPL with enzyme surface-modifying agents (polyethyleneimine or dodecyl aldehyde), co-aggregation with protein co-feeders (bovine serum albumin (BSA), and/or soy protein (SP)), use of silica magnetic nanoparticles functionalized with amino groups (SMNPs) as a separation aid, and starch as pore-making agent. The combination of enzyme surface modification with dodecyl aldehyde, co-aggregation with SMNPs and SP, in the presence of 0.8% (w/w) starch (followed by hydrolysis of the starch with α-amylase), produced pm-CLEAs of PPL with immobilization yield (IY) around 100% and recovered activities (RA) between 67% and 81% for the co-aggregates CLEAs with SMNPs/BSA (pm-BSA-CLEA) and SMNPs/SP (pm-SP-CLEA), respectively. The pm-SP-CLEA and pm-BSA-CLEA exhibited high stability at 40 °C and pH 8.0, retaining approximately 50% and 80% of activity, respectively, after 10 h of incubation, while free PPL was inactivated after 2 h. The morphological characterization of pm-SP-CLEAs and pm-BSA-CLEAs using scanning electron microscopy (SEM-FEG) showed the presence of non-uniform and porous structure, which could explain the high effectiveness factor (η ≈ 0.65), mainly for pm-CLEA of PPL prepared in presence of SP and SMNPs. Besides that, pm-SP-CLEAs showed good performance in tributyrin hydrolysis (52% yield in 4 h) and reutilization capacity (the hydrolysis yield of tributyrin decreased only 7% (from 52% to 45%) after five 4 h-batches). Thus, the strategies used in this work provided the CLEA with high mechanical and operational resistance, improvements in intraparticle mass transport, and ease of recovery and reuse of the biocatalyst.